The Effect of Providing Education on Gender Knowledge through Videos on Teenagers in the Prevention of Sexual Violence - Maryanah; Siti Masitoh; Maghfirotul Mahrid Dzikar (International Journal of Science and Society, 2022)
The purpose of this study was to determine the effect of providing knowledge about gender education through video to adolescents in the prevention of sexual violence. This research is a type of quantitative research using a quasi-experimental design with one group pretest and posttest design. This study uses a questionnaire instrument and a form of a test to measure basic abilities and achievements. Data collection techniques in this study are questionnaires and literature studies that produce primary data and secondary data. The data analysis technique in this study consisted of validity test, reliability test, univariate analysis, and bivariate analysis. The results of this study indicate that there is a significant difference between adolescents' knowledge about preventing sexual violence before being given education about gender through video media and after being given education about gender through video media with a value of 7.62 at pretest with a standard deviation of 4.62 and increasing to 14.06 with a standard deviation of 1.74 after the intervention of knowledge education about gender.